This is my brain in love - Gregorio, I. W. (New York : Little, Brown and Company, 2020)
Rising high school juniors Jocelyn Wu and Will Domenici fall in love while trying to save the Wu family restaurant, A-Plus Chinese Garden.
Keywords: Restaurants -- Fiction; Cooking, Chinese -- Fiction; Anxiety disorders -- Fiction; Chinese Americans -- Fiction; African Americans -- Fiction